Relationship Marketing: A Strategy for Marketing Programs to Diverse Audiences - Lisa A. Guion; Heather Kent (EDIS)
This paper is the eighth in a series of articles on planning programs to effectively outreach to diverse audiences. This series will include specialized papers on enhancing cultural competence, recruiting diverse volunteers, planning culturally appropriate marketing strategies, and other topics that are integral to the design and implementation of culturally relevant Extension education programs. This document is FCS9224, one of a series of the Family Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date Septmeber 2005.